THE PERIOD OF COORDINATED RELATIONS IN THE WORLD OF HUMAN PERCEPTION (IN THE ANALYSIS OF THE ANTHROPOCENTRIC ASPECT) (Conferencea, 2023)
In this article, on the example of Uzbek-language sources, the question of the world of human perception and gradual relationships in it is explored.